Two-dimensional superstructures of silica cages - Aubert, Tangi (2020)
Despite extensive studies on mesoporous silica since the early 1990s, the synthesis of two‐dimensional (2D) silica nanostructures remains challenging. Here, mesoporous silica is synthesized at an interface between two immiscible solvents under conditions leading to the formation of 2D superstructures of silica cages, the thinnest mesoporous silica films synthesized to date. Orientational correlations between cage units increase with increasing layer number controlled via pH, while swelling with oil and mixed surfactants increase micelle size dispersity, leading to complex clathrate type structures in multilayer superstructures. The results suggest that a three‐dimensional (3D) crystallographic registry within cage‐like superstructures emerges as a result of the concerted 3D co‐assembly of the organic and inorganic components. Mesoporous 2D superstructures can be fabricated over macroscopic film dimensions and stacked on top of each other. The realization of previously inaccessible mesoporous silica heterostructures with separation or catalytic properties unachievable via conventional bulk syntheses is envisioned.